Governance in Overcoming Gender-Based Cyber Violence: Case Study Bosnia and Herzegovina - Kunjaini, Anggi (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2023)
This study aims to analyze the governance of the Government of Bosnia and Herzegovina in overcoming gender-based cyber violence. Good governance in policy frameworks and institutional institutions is needed to meet cybersecurity needs in an inclusive and gender-sensitive manner. Using DCAF's simple security tools, the NAPRI tool helps its users analyze how the government of Bosnia and Herzegovina can apply the principles of good governance and gender inclusion. This study uses qualitative methods with descriptive analysis using secondary data. The findings of this study are that the legal framework of the Government of Bosnia and Herzegovina is regulated in the framework of gender equality, the framework of violence against women, criminal law, international treaties, and conventions. The law analyzes cybersecurity and gender mechanisms in Bosnia and Herzegovina. Institutional governance practices are catalysts for combating the gender effects of cybersecurity incidents and accelerating strategies to improve representation, oversight, decision-making, and service delivery.